Reparo do tendão do músculo gastrocnêmio de coelhos com enxerto de jejuno livre homólogo conservado em glicerina a 98% - Mastrantonio, Eneida César (2002)
Biological tissues obtained from different species and preserved by various methods have been successfully used in the tendon repair. Twenty-four male rabbits (Oryctolagus cuniculis) of the New Zealand race were used and divided in four groups containing six animais per group in order to evaluate the cicatricial repair of the tendon o f gastrocnemius muscle at 15, 30, 60 and 90 days post-surgery (PS). Thus, the tendon o f gatrocnemius muscle o f left (treated group) and right (control group) hindlimb o f all animais was sectioned and submitted to synthesis through Kessler modified suture and strengthening points. In the site o f the tenorrhaphy, the left hindlimb was involved by a homologous jejunum segment preserved in 98% glycerin. At the 15 days PS, the graft showed advaced reabsorption process with inflammatory infíltrate and neovascularization . After 15 days PS, it was observed an evolution in the cicatricial process with replacement of granulation tissue for modeled dense connective tissue and more organized and matured cicatricial tissue as compared to the control tendons. The homologous free intestinal segment without epithelium and lam ina própria of the mucous túnica, preserved in 98% glycerin, stimulated the fibroproliferation in the graft site. This method showed to be easy to perform and can be indicated in the repair of sectioned tendon of the gatrocnemius muscle in rabbits.